THE INFLUENCE OF CUSTOMER REVIEWS AND CUSTOMER RATINGS ON ONLINE PURCHASE DECISIONS ON THE SHOPEE MARKETPLACE - Gunawan, Iba (Universitas Banten Jaya, 2024)
The purpose of this study was to determine the influence of e-commerce shopee on product purchasing decisions for teenage users in Kosambi Village, Drangong Village. The method in this study uses primary data and secondary data. The primary data used is data obtained directly from Kosambi Village by means of observation, interviews, while secondary data is data obtained from literature studies and documentation related to the problems in this study. The population data for this study is 100 teenagers and the sample in this study is 80 respondents. The results of the discussion in this study, a simple linear regression analysis can be produced: The constant value of 29.187 indicates that the consistent value of the purchasing decision variable is 29.187. The coefficient value of 0.417 states that for every 1% increase in the e-commerce value of 0.417, the regression coefficient is positive, so it can be said that the direction of the x variable towards y is positive. the result of the calculation of the R Square value is 0.377 so that it can be stated that the influence between E-Commerce shopee on purchasing decisions is 37.7% while the remaining 62.3% is influenced by other factors not disclosed in this study.